The Application of an Indigenous Polymer for the Plastination of Teaching Anatomical and Biological Specimens (Indian Journal of Forensic Medicine & Toxicology, 2020)
Plastination was fabricated in 1978 by Dr. Gunther Von Hagens at the University of Heidelberg,, Germany,which Kept for the good conservation of anatomical and biological material. The present goal was to utiliz acost- effective plastination polymers as compared to the standard S10 technique using silicone polymers. TheS10 is the original silicone polymer used for the preparation of plastinated specimens and whole dissectingbody.. Specimens were fixed in formalin 10%, dehydrated and decreasing in acetone, and at last,impregnated bylocal commercial unsaturated polyester resin and ultimately hardening at 50 °C temperature.The plastinated specimens were clean, durable ,odorless ,portable and non-toxic ,it can be kept for longdurations without any changes .The usage of widespread S10 silicon method is high costs so with the aidof using indigenous chemicals it is possible to produced low costs anatomical models for education and forstudying anatomy.